Factorial Validity and Reliability of Self-Regulation Learning Questionnaire among Undergraduate Students at University of Dammam in Saudi Arabia - Malek M. Jdaitawi (Sultan Qaboos University, 2016)
The aim of the study was to examine the factor structure of the short-version of the self-regulated learning questionnaire in a group of undergraduate students at the University of Dammam. Four factors were assumed to represent the self-regulation: concentration, time management, self-testing and study aids. Testing reliability and validity of the constructs was another aim of this study. The study sample comprised 209 students (89 females and 120 males). Stu- dent age ranged from 18-21 years. The scale had 32 items with eight items for each of the four subscales. The research examined the factorial validity and reliability for the four factors of self- regulation across gender. The short version of the self-regulated questionnaire achieved good validity and reliability, and the confirmatory factor analysis (CFA) showed acceptable values of model fit to data. Consequently, the construct was compared via univariate analysis of variance with gender as independent variable. The results indicated significant differences between males and females. The contribution of this paper is to create a valid instrument to measure student self-regulation in university setting.